Adenosine production by brain cells. Issue 5 (6th April 2017) - Jackson, Edwin K.; Kotermanski, Shawn E.; Menshikova, Elizabeth V.; Dubey, Raghvendra K.; Jackson, Travis C.; Kochanek, Patrick M.
Abstract : The early release of adenosine following traumatic brain injury (TBI) suppresses seizures and brain inflammation. Using mass spectrometry we investigated in cultured neurons, astrocytes, and microglia the effects of oxygen‐glucose deprivation (OGD; models energy failure), H2 O2 (produces oxidative stress), and glutamate (induces excitotoxicity) on intracellular and extracellular levels of 5′‐AMP (adenosine precursor), adenosine, and inosine and hypoxanthine (adenosine metabolites). Neurons responded to OGD and excitotoxicity; microglia responded to oxidative stress; and astrocytes were mostly unresponsive. Developing therapeutics that recruit astrocytes to produce/release adenosine could have beneficial effects in TBI. Abstract: The early release of adenosine following traumatic brain injury (TBI) suppresses seizures and brain inflammation; thus, it is important to elucidate the cellular sources of adenosine following injurious stimuli triggered by TBI so that therapeutics for enhancing the early adenosine‐release response can be optimized. Using mass spectrometry with 13 C‐labeled standards, we investigated in cultured rat neurons, astrocytes, and microglia the effects of oxygen‐glucose deprivation (OGD; models energy failure), H2 O2 (produces oxidative stress), and glutamate (induces excitotoxicity) on intracellular and extracellular levels of 5′‐AMP (adenosine precursor), adenosine, and inosine and hypoxanthine (adenosine metabolites). In neurons, OGD triggered increases in intracellular 5′‐AMP (2.8‐fold), adenosine (2.6‐fold), inosine (2.2‐fold), and hypoxanthine (5.3‐fold) and extracellular 5′‐AMP (2.2‐fold), adenosine (2.4‐fold), and hypoxanthine (2.5‐fold). In neurons, H2 O2 did not affect intracellular or extracellular purines; yet, glutamate increased intracellular adenosine, inosine, and hypoxanthine (1.7‐fold, 1.7‐fold, and 1.6‐fold, respectively) and extracellular adenosine, inosine, and hypoxanthine (2.9‐fold, 2.1‐fold, and 1.6‐fold, respectively). In astrocytes, neither H2 O2 nor glutamate affected intracellular or extracellular purines, and OGD only slightly increased intracellular and extracellular hypoxanthine. Microglia were unresponsive to OGD and glutamate, but were remarkably responsive to H2 O2, which increased intracellular 5′‐AMP (1.6‐fold), adenosine (1.6‐fold), inosine (2.1‐fold), and hypoxanthine (1.6‐fold) and extracellular 5′‐AMP (5.9‐fold), adenosine (4.0‐fold), inosine (4.3‐fold), and hypoxanthine (1.9‐fold). Conclusion: Under these particular experimental conditions, cultured neurons are the main contributors to adenosine production/release in response to OGD and glutamate, whereas cultured microglia are the main contributors upon oxidative stress. Developing therapeutics that recruit astrocytes to produce/release adenosine could have beneficial effects in TBI.